Entropy, Carnot Cycle and Information Theory, Part 2 - Mario Martinelli (Entropy)
This second part of this companion paper the Carnot cycle is analyzed trying to investigate the similarities and differences between a framework related to thermodynamics and one related to information theory. The parametric Schrodinger equations are the starting point for the framing. In the thermodynamics frame, a new interpretation of the free energy in the isothermal expansion and a new interpretation of the entropy in the adiabatic phase are highlighted. The same Schrodinger equations are then applied in an information theory framework. Again, it is shown that a cycle can be constructed with a diagram that presents the Lagrange parameter and the average codeword length as coordinates. In this case the adiabatic phase consists of a transcoding operation and the cycle as a whole shows a positive or negative balance of information. In conclusion, the Carnot cycle continues to be a source of knowledge of complex systems in which entropy plays a central role.